FEATURES OF OXIDATIVE PROCESSES DISORDERS IN BACTERIAL-IMMUNE PERIODONTITIS ON THE BACKGROUND OF THE USE OF PROSTHETIC BASES - Demkovych, A. Ye.; Poliukhovych, Yu. I. (Eastern Ukrainian Medical Journal, 2025)
Introduction. In response to the use of dentures, chronic pathological processes of the mucous membrane, which serves as an entrance gate for microorganisms and denture components, may develop; as a result, lipid peroxidation processes and a decrease in the activity of antioxidant protection are observed. The purpose of this study was to examine the alterations in oxidative processes and the buildup of peroxidation products in rats with experimentally induced bacterial-immune periodontitis while utilizing removable dentures with acrylic and nylon bases.Methods. Experimental periodontitis was modelled in experimental animals by injecting into the periodontal tissues a suspension containing a mixture of microorganisms (Staphylococcus aureus and Streptococcus hemolyticus) based on egg white. Biochemical analysis of the activity of free radical processes (oxygen and nitrogen) in blood serum was performed, namely diene conjugates, triene conjugates, products of oxidative modification of proteins (neutral and basic), TBA-active products, and the level of nitrogen (II) oxide metabolites on the 30th day of the investigation both without and with different types of removable denture bases fixed in the oral cavity of experimental animals.Results. Throughout the study, it was determined that by the 30th day of the experiment, the inflammatory process in the periodontal complex led to a notable rise in lipoperoxidation products within the blood serum. This was evidenced by elevated levels of diene and triene conjugates, TBA-active compounds, and oxidatively modified protein products. Analysis of changes in lipoperoxidation indicators in the blood serum of experimental animals with inflammation and different types of prosthetic bases shows that the level of reactive oxygen species increased compared to the control group. However, the indicators were lower than in animals without the use of bases, which indicates the preservation of free radical processes and a violation of the dynamic balance between oxidative stress and antioxidant protection.Conclusion. Inflammation in the periodontal complex, driven by bacterial-immune factors, is characterized by heightened oxidative stress, homeostatic imbalance, and accelerated production of lipoperoxidation products. The use of acrylic and nylon bases leads to a decrease in the concentration of peroxidation products, but inflammatory activity remains.